Improved adsorption of Congo red by nanostructured flower-like Fe(II)-Fe(III) hydroxy complex - Sun, Xiaoyan (Water science and technology : a journal of the International Association on Water Pollution Research, 2018)
Amorphous Fe(II)-Fe(III) hydroxy complex with flower-like nanostructure was synthesized by ferric reduction using a microwave-assisted ethylene glycol approach. Here we investigated the correlation between its chemical composition and the removal rate for Congo red (CR) dye. The results showed that the amorphous complex had similar reduction and anion exchange capacities to the green rust. Due to the synergistic effect of attractive electrostatic interaction, anion exchange, ferrous redox and hydrogen bonding, the Fe(II)-Fe(III) hydroxy complex exhibited strong adsorption of CR with an estimated adsorption capacity up to 513 mg g-1. In contrast, the Fe(III) hydroxy complex had an adsorption capacity of 296 mg g-1 because of the predominant mechanism based on the electrostatic interaction. The present study provides a facile synthesis of nanostructured iron hydroxy complex, with superior performance in adsorbing CR